Strategi dan Tingkat Kepekaan Bilangan Siswa Sekolah Dasar Dalam Menyelesaikan Masalah Operasi Bilangan Bulat - Putrawangsa, Susilahudin; Hasanah, Uswatun (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
The current research intends to both identify students’ strategies and clarify the level of students’ number sense expression of primary students in solving problems relating to addition, subtraction, and multiplication of integers. This is a qualitative research. Five respondents are involved which are randomly taken from a primary school in Lombok Island. The data are collected through test. Meanwhile, data analysis utilize three indicators of number senses in order to answer two main research questions. The findings indicate that, firstly, the strategies used by the students to solve problems relating to addition, subtraction, and multiplication are homogenous, routine and standardized which are algorithm or procedure oriented, such as column addition, column subtraction, and column multiplication, respectively. Secondly, according to the four level of number sense expressions ─such as ‘not yet evident’, emerging, expressing, and excelling─, the findings indicate that the students’ level of number sense expression is categorized as ‘not yet evident’, which is the lowest level of the four level.